2022
DOI: 10.4274/ejbh.galenos.2022.2022-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Arab Cultural Barriers That Influence Muslim Arab Iraqi Women’s Breast Cancer Screening Behavior

Abstract: Key Points •Breast cancer is the most common type of cancer in Iraqi women and breast cancer screenings are very crucial for early detection.• Cultural spesific barriers may effect women's breast cancer screening behaviors.• Culturally specific barriers of women that might prevent breast cancer screening need to be determined by health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Platforms like Instagram and Facebook expose women to images of idealized beauty, leading to internal conflicts and a stronger desire for cosmetic procedures such as liposuction. Studies have shown that women who frequently use social media and follow beauty influencers are more likely to consider cosmetic surgery to achieve these beauty ideals [ 4 , 5 ].…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…Platforms like Instagram and Facebook expose women to images of idealized beauty, leading to internal conflicts and a stronger desire for cosmetic procedures such as liposuction. Studies have shown that women who frequently use social media and follow beauty influencers are more likely to consider cosmetic surgery to achieve these beauty ideals [ 4 , 5 ].…”
Section: Editorialmentioning
confidence: 99%
“…Social media platforms such as Instagram and Facebook expose women to global beauty trends, increasing the desire for cosmetic enhancements. This exposure often leads to internal conflicts between modern beauty ideals and traditional values [ 4 ]. The influence of social media is evident in the increasing number of women seeking cosmetic enhancements to align with perceived international standards of beauty.…”
Section: Editorialmentioning
confidence: 99%